Effects of long-term phosphate fertilization on potential risks of emerging contaminants in agroecosystems of the eastern Amazon, Brazil. Issue 1 (31st December 2022) - Braz, Anderson Martins de Souza; da Costa, Marcondes Lima; Ramos, Sílvio Junio; Pereira, Wendel Valter da Silveira; Rizzo, Rodnei; Fernandes, Antonio Rodrigues
ABSTRACT: This study aimed to assess the levels of rare earth elements and yttrium (REY) and vanadium (V) in soils cultivated with citrus, oil palm and black pepper in the eastern Amazon . The potential risk of contamination was estimated using the enrichment (EF) and bioaccumulation (BAF) factors. The results showed that pH, K, and P significantly affected the REY concentrations. The bioaccumulation of europium was the most significant among the studied elements. The contents of V were positively correlated with pH and Fe and K oxides. The EF and BAF of V followed the order: EF – black pepper (2.95) > oil palm (2.77) ≫ citrus (0.57); BAF – citrus (0.091) > black pepper (0.023) > oil palm (0.018). The increase in REY and V does not pose current risks in the study area. However, these results may support the monitoring of environmental contamination, prevention, and control of emerging contaminants by government agencies. Graphical abstract: uf0001